2022
DOI: 10.1186/s12910-022-00846-0
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Polish physicians, nurses and pharmacists towards the ethical and legal aspects of the conscience clause

Abstract: Background While healthcare professionals’ right to invoke the conscience clause has been recognised as a fundamental human right, it continues to provoke a heated debate in Polish society. Although public discourse is filled with ethical and legal considerations on the conscience clause, much less is known about the attitudes of healthcare professionals regarding that matter. The aim of this study was therefore to describe the attitudes of Polish physicians, nurses and pharmacists towards the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For example, in 2014, nearly 4000 Polish physicians and medical students signed the Declaration of faith of Catholic doctors and students of medicine on the sexuality and fertility of human beings, in which they recognized superiority of ‘God’s law’ over the law of nations (Półtawska, 2015 ). Consequently, some physicians and nurses object to performing legal abortions, prenatal screening tests, contraceptives, or assisted reproduction techniques (Baranowska et al, 2012 ; Czekajewska et al, 2022 ; Zaręba et al, 2020 ). Alternatively, Pawlikowski et al ( 2012 ) demonstrated that, while religiosity positively affects physicians’ altruism, empathy, and holistic approach toward patients, it often clashes with respect for the patient’s autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 2014, nearly 4000 Polish physicians and medical students signed the Declaration of faith of Catholic doctors and students of medicine on the sexuality and fertility of human beings, in which they recognized superiority of ‘God’s law’ over the law of nations (Półtawska, 2015 ). Consequently, some physicians and nurses object to performing legal abortions, prenatal screening tests, contraceptives, or assisted reproduction techniques (Baranowska et al, 2012 ; Czekajewska et al, 2022 ; Zaręba et al, 2020 ). Alternatively, Pawlikowski et al ( 2012 ) demonstrated that, while religiosity positively affects physicians’ altruism, empathy, and holistic approach toward patients, it often clashes with respect for the patient’s autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…This is also the case for other countries. Czekajewska et al very recently stated, ‘while the conscience clause is rarely invoked in Poland, most healthcare professionals declare that the current legal regulations in that sphere are unclear and inaccurate’ [ 22 ]. Dobrowolska et al state, ‘Regulation in the United Kingdom is limited to reproductive health, while in Poland, there are no specific procedures to which nurses can apply an objection’ [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research from across Europe has argued strongly for and against conscientious objection in nursing, with the arguments against it being mostly related ‘to organizational aspects of its application’ [ 20 ]. In that regard, Czekajewska et al recently stated that while in Polish society there is an ongoing heated debate on nurses’ right to invoke their conscientious objection, little is known about their attitudes towards that matter [ 22 ]. Much of the same holds for Greece, where little is known about the perceptions and lived experiences of nurses who have ethical concerns and conscientious objections in clinical practice.…”
Section: Conscientious Objection In Nursing: the Greek Normative Fram...mentioning
confidence: 99%
“…Others reject these arguments and claim that the clash of JWs’ values and those held by HCPs do not implicitly make their decision wrong and that the assessment of JWs’ competence should be based on their ability to make decisions rather than on the decisions themselves [ 33 , 34 ]. At the same time, research shows that, as Polish physicians and nurses face ethical and other non-medical difficulties in making clinical decisions, many are still embedded in a paternalistic tradition of practicing medicine [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%